Ilyocypris (Crustacea: Ostracoda) species in North East Asian rice fields; description of one new species, and redescriptions of Ilyocypris dentifera Sars, 1903 and Ilyocypris japonica Okubo, 1990 - Smith, Robin James; Zhai, Dayou; Chang, Cheon Young (Zootaxa, 2019)
Ilyocypris species are abundant and widespread in North East Asian rice fields, but for many species their taxonomy is poorly defined, which negatively impacts ecological studies on rice field ecosystems. Herein, two of these species, Ilyocypris dentifera Sars, 1903 and Ilyocypris japonica Okubo, 1990, are redescribed, and a third species, Ilyocypris incus sp. nov., is described and named. This latter species has previously been reported from Japan and possibly Korea under the names Ilyocypris angulata Sars, 1903 and I. dentifera, but study of the hemipenes demonstrates that it is a separate species. Ilyocypris nipponica Okubo, 2004 nomen nudum previously reported from Japan is herein considered to be a junior synonym of I. dentifera. Tuberculated and non-tuberculated forms of both I. dentifera and I. japonica were recovered during this study and the presence or absence of tubercles is postulated to be related to environmental conditions, such as water chemistry or predation pressures. Although tuberculated forms of I. dentifera do occur, we concur with some previous studies that Ilyocypris angulata Sars, 1903 should be treated as a separate species, based on features of the hemipenes and carapaces. Figures of the carapaces and hemipenes of I. angulata, and Ilyocypris mongolica Martens, 1991, which is morphologically very close to I. japonica, are also presented for comparisons. This study confirms that three species of Ilyocypris inhabit North East Asian rice fields: I. dentifera, I. japonica and Ilyocypris incus sp. nov. Extant Ilyocypris species in North East Asia, including those from habitats other than rice fields, can be divided into two groups based on the Zenker organ, hemipenis, and sixth limb morphologies. These groups are postulated to represent two distinct lineages of Ilyocypris in North East Asia.